1995
DOI: 10.1111/j.1365-2621.1995.tb09812.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Ascorbic Acid Loss and Nonenzymatic Browning in Orange Juice Serum: Experimental Rate Constants

Abstract: The kinetics of ascorbic acid loss and nonenzymatic browning in clarified orange juice (serum) were investigated in an anaerobic environment from 70.3 to 97.6"C and from 11.7 to 80.6"Brix. Data were fitted to firstorder kinetic models. Rate constants of ascorbic acid degradation in serum were not different from rate constants in whole juice. Activation energies were -30 kcal/mol and largely independent of solids concentration. Rate constants of browning pigment formation were 30-50% greater in serum. Activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
4
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 23 publications
11
92
4
2
Order By: Relevance
“…The activation energy for AA degradation was found as 55.30 kJ/mol. This value is higher than the values of 47.5 kJ/mole for rosehip pulp (Karhan et al 2004) heated under anaerobic circumstances (70-95 ºC), 15.7 kJ/mol for raspberry pulp (Summen & Erge 2014) heated at 60-90 ºC, and lower than the value of 115.5 kJ/mole for orange juice (Johnson et al, 1995) but in good agreement with the activation energies (35.9-94.0 kJ/mol) for ascorbic acid degradation (Dhuique-Mayer et al, 2007;Lima et al, 2010).…”
Section: Thermal Degradation Of Aa Th and Rb In Rhnmentioning
confidence: 48%
“…The activation energy for AA degradation was found as 55.30 kJ/mol. This value is higher than the values of 47.5 kJ/mole for rosehip pulp (Karhan et al 2004) heated under anaerobic circumstances (70-95 ºC), 15.7 kJ/mol for raspberry pulp (Summen & Erge 2014) heated at 60-90 ºC, and lower than the value of 115.5 kJ/mole for orange juice (Johnson et al, 1995) but in good agreement with the activation energies (35.9-94.0 kJ/mol) for ascorbic acid degradation (Dhuique-Mayer et al, 2007;Lima et al, 2010).…”
Section: Thermal Degradation Of Aa Th and Rb In Rhnmentioning
confidence: 48%
“…No tocante ao aspecto nutricional e estabilidade de produtos alimentícios um bom controle de qualidade em função de ácido ascórbico é fundamental [7,8,13,15]. Os testes de laboratório mostraram que no intervalo de tempo entre 0,0 a 4,0 horas de aquecimento (100 o C) o teor original de ácido ascórbico na cajuína diminui em torno de 48% como pode ser observado na Tabela 3.…”
Section: -áCidosunclassified
“…Com base nos resultados pode-se sugerir que 2,0 horas de aquecimento é um tempo adequado para esterilizar à bebida e não alterar significativamente o teor de vitamina C. Estudos paralelos com solução sintética de cajuína indicaram que a degradação do ácido ascórbico provavelmente possui influência na cor da bebida cajuína. Os trabalhos de JOHNSON, BRADDOCK, CHEN [7] e KACEM et al [8] sobre a cinética de degradação e reações não enzimáti-cas do ácido ascórbico, indicam a participação do mesmo na formação de cor em suco de laranja.…”
Section: -áCidosunclassified
“…Pasteurization has some impacts on the quality of lemon juice, such as the loss of color, flavour, nutritional value and taste (Espachs-Barroso et al 2006). Ibarz et al (2009) reported that nonenzymatic browning caused by Maillard reaction (formation of HMF and furfural) affects the quality of fruit juices negatively, affecting its organoleptic properties, such as texture, color, taste and flavor, and nutritional quality, including the contents of vitamins, sugars and other minority compounds (Toribio and Lozano 1986;Johnson et al 1995;Urbicain et al 1999;Buedo et al 2001).…”
Section: Higlightsmentioning
confidence: 99%